Culture, Social Cooperation and Negotiation - Caloca Osorio, Oscar (2015)
This research combines our interests in the cultural economy, largely poured solidarity, that is, the distance of only competitive economy. In this sense, we move away from the principle of rationality and reasonableness we approach, which  involves a consideration of competition and social cooperation. This distance allows viewing the negotiation process from another perspective, in particular, from the existence of community, guided by the principle of state of cognitive beliefs and common knowledge.